2008
DOI: 10.1007/s10806-008-9116-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Scope of Farmer Perceptions of Risk: Considering Farmer Opinions on the Use of Genetically Modified (GM) Crops as a Stakeholder Voice in Policy

Abstract: In the beginning, policy debates between critics and advocates of genetically modified (GM) crops focused on scientifically determined risks. Ten years later, the argument between environmentalists or consumers and regulators or industry has changed into a discussion about the implementation of more democratic policymaking about GM farming. A notable omission from the political debate about food biotechnology in the United States, however, is the opinion of farmers who cultivate the GM crops. Policymakers shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…In other cases, farmer perception of risk was mitigated by scientific information from trusted agencies such as government extension agents or university researchers. 12 The following responses are consistent with this observation:…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In other cases, farmer perception of risk was mitigated by scientific information from trusted agencies such as government extension agents or university researchers. 12 The following responses are consistent with this observation:…”
Section: Resultssupporting
confidence: 74%
“…12 Debates have been dominated by environmentalists, scientists, policy makers and regulators. 8 Absent from the debate even in countries where GM crops have been grown the longest (in the US), are the voices of farmers who are the direct users of the technologies 12 Previous studies of farmers in industrialized countries suggest that farmers' decisions about whether or not to adopt GE crops extend beyond economic considerations. Their practical knowledge of agricultural challenges faced in the field may help to resolve disputes between stakeholders who are removed from participating directly in agriculture but are heavily engaged in the debate.…”
Section: Introductionmentioning
confidence: 99%
“…Areal, Riesgo, and Rodriguez-Cerezo (2011) concluded that, for EU farmers, the potential financial gains were important in the decision to adopt GM herbicide-tolerant crops, as did Breustedt, Muller-Scheeßel, and Latacz-Lohmann (2008) for German arable farmers adopting GM oilseed. However, Guehlstorf (2008) in a study in the USA, concluded that farmers were influenced by environmental considerations and social impact, as well as financial gains.…”
Section: Introductionmentioning
confidence: 99%
“…It also means that a new relationship between and integration of agriculture, sustainability, environment, and ethics will be needed (Meester et al 2005;Weis 2010). It must include the social consequences of the policy implemented (De Hoogh 1991;Jochemsen 2008), not least indicating renewed attention to the opinions of farmers themselves (Guehlstorf 2008;Visser 2010). This new ethical attitude should also pay critical attention to the assistance provided to Third World countries towards modernizing and rationalizing their agriculture, perhaps more for political than for ideological reasons (e.g., the Green Revolution, as described by Cullather (2004) and Hamblin (2009)).…”
Section: Discussionmentioning
confidence: 99%